Executive functioning in relapsing-remitting multiple sclerosis patients without cognitive impairment: A task-switching protocol. (September 2018) - Migliore, Simone; Curcio, Giuseppe; Couyoumdjian, Alessandro; Ghazaryan, Anna; Landi, Doriana; Moffa, Filomena; Quintiliani, Livia; Squitieri, Ferdinando; Palmieri, Maria Giuseppina; Filippi, Maria Maddalena; Vernieri, Fabrizio
Background: Cognitive dysfunction affects 40%–65% of multiple sclerosis (MS) patients, most often affecting information processing speed and working memory, mediated by the pre-frontal cortex (PFC). Objective: Our study aimed to investigate PFC functioning through a task-switching protocol in relapsing-remitting multiple sclerosis (RRMS) patients without cognitive impairment. Methods: A total of 24 RRMS patients and 25 controls were enrolled. Two different tasks were performed in rapid and random succession, so that the task was either changed from one trial to the next one (switch trials) or repeated (repetition trials). Switch trials are usually slower than repetitions, causing a so-called switch cost (SC). Results: Patients had worse performance than controls only in the switch trials, as indicated by increased SC and reaction times. Moreover, patients showed a reduced ability to reconfigure the task-set for the execution of a new task and to disengage from the previous one. Conclusion: Our results showed a primary deficit in executive control processes involved in the task-switching performance in RRMS patients without cognitive impairment. This deficit may depend on the functional impairment of the PFC, which is essential to adjust behaviour rapidly and flexibly in response to environmental changes, representing one of the most sophisticated human abilities.